Economia verde e economia circular: desafios e oportunidades - Ribeiro, Anabela Vaz (2020)
ISEP, through CIDEM (Center for Research and Development in Mechanical Engineering), is a co-promoter of the “PME Sustentável” (Sustainable SME) project. This project, funded under the COMPETE 2020 / FEDER, aims to strengthen the competitiveness of Portuguese small and medium-sized enterprises (SMEs) by promoting the adoption of a circular economy. The Sustainable SME project has emerged from the need to respond to the challenges arising from the EU Directive 2014/95 / EU, which consists of the disclosure by companies of information not included in the traditional financial report. It is intended that organizations also disclose data on sustainability (social and environmental factors).The results of the study are compiled in this book.